Third and Fourth Branchial Arch Anomalies in Children: Insights from a Tertiary Care Center - Abhinav Sihag; Lakshmi Sundararajan; S. Thirunavukkarasu (Journal of Indian Association of Pediatric Surgeons)
Background and Aim: The third and fourth branchial cleft and pouch anomalies are the rarest among the anomalies of branchial arches and can pose diagnostic and management challenges in pediatric patients. Our study aimed to describe the clinical presentation, management, and treatment outcomes of the third and fourth branchial cleft and pouch anomalies over a 10-year period in our hospital. Materials and Methods: A retrospective analysis was conducted on pediatric patients aged 1–18 years who underwent otolaryngologic and pediatric surgical interventions for the third and fourth branchial cleft and pouch anomalies from 2013 to 2022. Clinical data including age, gender, presenting symptoms, age of onset of symptoms, laterality, imaging findings, surgical procedures, complications, and follow-up outcomes were collected, and the database was maintained. Results: Eleven pediatric patients (5 females and 6 males) with a mean age of 4 years (range: 1–9 years) were identified. Common presenting symptoms included neck swelling and recurrent neck infections. Diagnosis was established based on imaging findings on ultrasound and magnetic resonance imaging (MRI)/computed tomography neck aided by suspension microlaryngoscopic visualization of internal opening in the pyriform sinus. Surgical excision of the tract with/without partial thyroidectomy along with endoscopic ablation/cauterization of pyriform sinus opening was the primary treatment modality, with favorable outcomes and no complications. No recurrence was reported during follow-up. Conclusions: A high index of clinical suspicion coupled with MRI and microlaryngoscopic evaluation is vital for accurate diagnosis of these lesions. Treatment should prioritize complete excision of the tract while quiescent. Internal opening ablation/cauterization reduces the risk of recurrence.